Xeno-Hybrid Bone Graft Releasing Biomimetic Proteins Promotes Osteogenic Differentiation of hMSCs - Zhu, Hao; Blahnová, Veronika Hefka; Perale, Giuseppe; Xiao, Jun; Betge, Felice; Boniolo, Fabio; Filová, Eva; Lyngstadaas, Ståle Petter; Haugen, Håvard Jostein (Frontiers in Cell and Developmental Biology, 2020)
Bone defect is a significant health problem worldwide. Bone is also the second most transplanted tissue after blood. Myriad bone grafts are designed and applied in clinics. Limitations, however, from different aspects still exist, including limited supply, mechanical strength, and bioactivity. In this study, two biomimetic peptides (P2 and P6) are incorporated into a composite bioactive xeno hybrid bone graft named SmartBonePep®, with the aim to increase the bioactivity of the bone graft. The results, which include cytotoxicity, proliferation rate, confocal microscopy, gene expression and protein qualification, successfully prove that the SmartBonePep® has multi-modal biological effects on human mesenchymal stem cells from bone marrow. The successful physical entrapment of P6 into a composite xeno-hybrid bone graft, withstanding the manufacturing processes including exposure to strong organic solvents and ethylene oxide sterilization, increases the osteogenic potential of the stem cells as well as cell attachment and proliferation. P2 and P6 both show a strong biological potential and may be future candidates for enhancing the clinical performance of bone grafts.